DAMPAK KEBIJAKAN PEMERINTAH TERHADAP PEMBANGUNAN EKONOMI D. I. YOGYAKARTA 2001-2017: Simulasi dengan Analisis Sistem Persamaan Simultan - Anissa Dika Larasati; Vera Lisna (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2020)
Economic development includes increasing economic growth and alleviating poverty. D.I Yogyakarta is a province with the lowest economic growth and per capita income compared to other provinces in Java. Besides, it has the highest poverty rate. With this condition, it is feared that economic development and economic contribution in D.I Yogyakarta which are relatively low are difficult to increase. This study aims to analyze the simultaneous relationship between indicators of economic development in the province of D.I Yogyakarta, explores the variables that influence it, and perform policy simulations to improve economic development. The indicators used to describe economic growth in this study are Regional Gross Domestic Product (regional GDP), household consumption, and community savings in banks. While the indicators that are used to reflect the poverty level are the percentage of poor people. The estimation method used is simultaneous Two-Stage Least Squares (2SLS) equation system which consisted of three structural equation and one identity equation using the historical data from the year 2001-2017. The results of the simulation show a 6% increase in government expenditure can improve economic growth to 5.41% and reduce the percentage of poor people by 0.41% points.